Responsabilidade social empresarial: modalidades e grau de participação em meios de hospedagem em Ponta Negra, Natal/RN - Graciano, Cláudia Gomes (2009)
That work has as objective to investigate and to analyze the strategies which they were developed by companies of lodging means with ends of social responsibility in Rio Grande do Norte (RN). Therefore, it got data along with the Office of Tourism of the Municipal district of Natal , the Office of Tourism of RN and the cadasters of the firms of the lodging means in the district of Ponta Negra. In after research of field, it verified the enterprises that now develop lodging activities in that quarter in Ponta Negra. It applied Instrument of research which it was elaborated based on the set of indicators of social responsibility of Ethos Institute, structured with binary questions and some open ones. It shows as results which actions the investigated companies develop. Confronting these results with researched theoretical referencial, it points an intermediate degree of socially responsible actions. Comparing with the evaluation accomplished by Ethos Institute, the investigated firms are in incipient condition, with punctual actions, however, they already present the awakening about this thematic